Evidence of melt– and fluid–rock interactions in the refractory forearc peridotites and associated mafic intrusives from the Tuting–Tidding ophiolites, eastern Himalaya, India: Petrogenetic and tectonic implications. (23rd November 2020) - Dutt, Amrita; Singh, Athokpam Krishnakanta; Srivastava, Rajesh K.; Oinam, Govind
Abstract : We present a comprehensive geochemical data set of whole‐rock geochemistry and mineral phases from the mantle peridotites and mafic intrusives of the Tuting–Tidding Suture Zone (TTSZ) ophiolites, eastern Himalaya, north‐east India. Modal mineralogy, low Al2 O3 and CaO, high Cr# of Cr‐spinels, and forsterite number (Fo90–92 ) in primary olivine indicate the highly refractory nature of the TTSZ peridotites. LREE‐enriched patterns, cumulative olivines in dunites, and Cr‐spinel and olivine compositions further suggest that the peridotites were subjected to high‐temperature melt–rock interaction from a percolating boninitic melt in the nascent forearc of an intra‐oceanic subduction zone. The associated mafic intrusives are tholeiitic in nature and their geochemical characteristics [∑REE = 23.34–59.12; nearly flat rare earth elements (REE) pattern (LaN /YbN = 1.49–2.58); negative anomalies of Nb and Ti] show mid‐oceanic ridge basalt affinity. Trace elemental modelling of the mafic intrusives along with their mineralogy and geochemistry suggests that they formed due to different degrees of partial melting with the involvement of a subduction component in the spreading regime of the forearc region. Based on the presence of hydrous minerals like Cr‐chlorite and tremolite in the peridotites and P–T modelling (525–575°C, 1.05–1.09 GPa) of the mafic intrusives, it is considered that TTSZ ophiolites underwent low‐temperature metamorphism by fluid–rock interaction either during the later phase of subduction (in a cool mature subduction zone) or during Himalayan Orogeny. We also infer that the TTSZ ophiolites resemble other Neo‐Tethyan ophiolites of the Indus‐Tsangpo Suture Zone in terms of their geochemical and petrogenetic aspects. Abstract : REE characteristics, cumulative olivines in dunites, and Cr‐spinel and olivine compositions suggest that the mantle peridotites of Tuting–Tidding Suture Zone (TTSZ) ophiolites, eastern Himalaya were subjected to high‐temperature melt–rock interaction from a percolating boninitic melt in the nascent forearc of an intra‐oceanic subduction zone. Trace elemental modelling along with their mineralogy and geochemistry of the associated mid‐oceanic ridge basalt‐type mafic intrusives suggests that they formed due to different degrees of partial melting with the involvement of a subduction component in the spreading regime of the forearc region. It is considered that TTSZ ophiolites underwent low‐temperature metamorphism by fluid–rock interaction either during the later phase of subduction (in a cool mature subduction zone) or during Himalayan orogeny.